PENGARUH LABA DAN KETERSEDIAAN KAS TERHADAP KEPUTUSAN INVESTASI (Studi Kasus di Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Apriani, Risa (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2022)
ABSTRACK This study aims to examine and analyze whether earnings and cash availability either partially or simultaneously affect investment decisions in manufacturing industrial companies listed on the Indonesia Stock Exchange and to find out what factors influence investment decisions from the two factors studied. This investment decision relates to the use of sources of funds within the company for a certain period of time in the hope of making a profit. This study uses 18 samples of companies. The data source is secondary data obtained from the Indonesia Stock Exchange (IDX). The hypothesis was tested with multiple linear regression models and data processing using the SPSS 21 program. The results showed that profit had an effect on investment decisions while cash had no effect, but simultaneously earnings and cash had an effect on investment decisions.